An object stays at rest unless acted upon by an unbalanced force: how pension auto-enrolment and the force of inertia cause debt - Brown, Adrian (2024)
Does being automatically enrolled into a pension lead to an increase in debt? This is vital to investigate since the scheme's purpose is to give people more money for retirement and not for them to have a large pension that is offset by the unintended consequence of more debt. Literature in this area has given seemingly contradictory results. This paper seeks to address this by proposing an explanation for these differences – inertia. This paper explains how using a data set used by Gathergood et al. (2024), it would be possible to test if the theoretical argument of inertia may explain the literature’s findings. This paper does not have access to Gathergood et al. (2024) data, so it discusses how the data and hypothesised results could be analysed. If the theoretical argument of this paper is upheld by the data, then this research would provide policymakers with the insights needed to design auto-enrolment pension schemes that effectively avoid the unintended side-effect of debt.